O empreendedorismo educacional e o impacto sobre as atitudes e intenções empreendedoras em alunos brasileiros de MBA - Zardo Junior, Egídio (2019)
The validity and effectiveness of educational entrepreneurship programs have been tested and proven by several studies conducted in developed countries, analyzing how they influence student's attitudes and intentions in creating their own initial business: startups. However, few studies with this objective have been carried out in the context of emerging countries (especially in Brazil), thus helping to broaden the understanding of the impact of such programs. Based on the theory of planned behavior, this research evaluated whether the impact of an educational entrepreneurship program (mandatory and of short duration) on the entrepreneurial attitudes and intentions of students at a Brazilian college is distinct from the impact of similar programs, applied in countries developed countries. A quantitative research, based on primary data, was applied to 418 students from 24 MBAs courses, graduated between 2014 and 2018. Variable analysis was performed through structural equation modeling (partial least squares method). Among the main conclusions, the hypothesis that the program directly and positively impacted both the attitudes and the entrepreneurial intention of the students to create startups was confirmed, which demonstrated its effectiveness. In addition, research has shown that the student's previous experience in entrepreneurship positively moderates the association between the effect of the entrepreneurship program and his entrepreneurial attitudes, that is, if the student had any previous experience in entrepreneurship, the greater the effect of the program on their entrepreneurial attitudes. This contradicts findings from other previous research carried out in developed countries, which demonstrated the opposite. This result points to a new perspective and to the need for further studies on the impact of students' previous entrepreneurial experiences in developing countries, in order to broaden the understanding of the topic in different contexts.